Symposium 3: Trans-National Online Activities For Students – A Pragmatic Approach - Bell, Frances; Whatley, Janice; Zakrzewska, Danuta (Proceedings of the International Conference on Networked Learning, 2004)
E-learning has opened up additional opportunities for internationalising the curriculum in Higher Education, an endeavour that has many dimensions, including those of culture and pedagogy. Graduates’ need to operate effectively in multi-cultural societies and global business environments is relevant to many disciplines, and to campus-based as well as distance learning students. We examine the drivers for internationalising the curriculum within the context of the growth of the Internet and the increasingly global market for Higher Education. We present a pedagogical model and a set of guidelines that can be used to design trans-national online student collaboration, and discuss how these can be operationalised in a selection of scenarios for internationalisation of the curriculum. Lastly we encourage colleagues at Institutions across Europe to build on our work by adapting and refining our model and guidelines, and integrating activity-based approaches with broader strategies for internationalisation of the curriculum.